原住民族小學民族教育課程實施之個案研究A Case Study of the Implementation of the Ethnic Education Curriculum in An Aboriginal Elementary School - 周水珍Shui-Jen Chou (Higher Education Foundation, 2007)
本研究旨在觀察一所太魯閣族原住民學校發展民族教育課程的過程，以理解當前原住民民族教育課程的實施情形，研究方法採文獻分析法及個案研究法。全文 內容共分五部分，首先說明研究的動機與目的；其次探討民族教育課程的相關理論 與研究；續次說明研究方法與歷程；接著呈現個案研究資料的分析結果與討論研究 發現；最後則為結論與建議。研究結果顯示，太魯閣族原住民學校的族群文化課 程，在課程形式方面包括：正式課程、非正式課程及潛在課程；在課程實施方面： 採自編教材、融合式課程與附加式課程，以及課程實施的困境。本研究並依研究發 現提出改進原住民族學校發展民族教育課程的建議。 The purpose of this study is to promote the understanding of how aboriginal ethnic education is implemented in schools, based on the observation of the tribal curriculum development process occurring in a Truku elementary school. The main research methods are literature review and case study. There are 5 sections in this article. Research purpose is described first, followed by a review of ethnic education curriculum theory and related research. Research methods and data collection methods were introduced in the third section. Data analysis results, research findings and discussion are presented in the fourth section and several recommendations are offered in the conclusion section. The research results reveals: (a)The Truku ethnic education curriculum can be categorized as formal, informal and hidden curriculum. (b)The curriculum implement can be included as selfdeveloped teaching materials, infused curriculum and additional curriculum. (c)The dilemmas of curriculum implement. Based on the research findings, the researcher offers several suggestions in the conclusion section for facilitating ethnic education curriculum in aboriginal elementary schools. Keywords: aboriginal elementary schools, ethnic education curriculum, curriculum implement.